PENINGKATAN PEMAHAMAN KONSEP FISIKA BERBASIS PHET SIMULATION MATA KULIAH FISIKA MODERN - Ferawati Artauli Hasibuan (Fakultas Keguruan Dan Ilmu Pendidikan, UM-Tapsel, 2020)
The research had done in sixth (VI) semester students of Physics Education Program, Faculty of Teacher Training and Education, University of Graha Nusantara Padangsidimpuan 2018/2019 Academic Year, the total is 20 people. Researchers applied PhET Simulation Interactive based learning by using computers with modern physics material. The type of research is Classroom Action Research that conducted in two cycles. The purpose of this study was to find out the increasing of understanding student concepts through the application of PhET-based learning media, due to the learning of Modern Physics and it was hoped that students would be able to follow the development of knowledge and technology, one of them is nanotechnology. The learning media that used in this study are Lesson Plan (RPP), Instruments, student activity observation sheets, and observation sheets of the lecturers’ ability to manage learning. Furthermore the test and activity of observation sheet were used to determine the level of students' understanding of the physics concept. The test that used is an essay test that had been tested with the reliability of the first cycle test is 0.79 and the second cycle test is 0.83 with a high level of reliability. Both tests have 5 valid questions. The conclusions of this study are (1) The use of PhET simulation-based learning media can improve the understanding of students’ physics concepts in modern physics subjects. (2) The use of PhET simulation-based learning media can improve the ability of lecturers to manage learning in PhET simulation subject at UGN Padangsidimpuan.